Pengembangan Game Edukasi Menggunakan Adobe Flash CS6 Untuk Anak Usia Dini Dengan Menerapkan Model Skenario Petri Net - Deli Deli (Telcomatics, 2018)
Petri Net is one of the models to represent a distributed system and is widely used in areas such as process control, computer networks, queuing systems, and others. In the field of informatics, petri net was also used for system modeling in the development of interactive multimedia. Learning Media that would become one of the means for children in the learning process. In influence of the development of information technology, the media will be developed through educational games. One media that can assist in the delivery of interactive media content is accompanied by educational game. The resulting product is a CD that accompanied Interactive educational games inside. Based on the results of this design, it is advisable for parents and teachers to introduce this communication medium to the children because this product has advantages as a medium of learning easy and attract children to learn, especially for children an early age. Expected media in particular can also help the child to learn to recognize numbers and letters easily, distinguish colors and can recognize animals and fruits.